1 - Towards Academic Freedom for Africa in the 21st Century* - Mama, Amina (Journal of Higher Education in Africa, 2022)
This paper begins by reviewing the ways in which the higher education landscape in Africa has changed significantly during the last decade as a result of the ongoing regional crisis and the changing perspectives on African higher education articu- lated within the international development arena and argues that, if the higher edu- cation crisis of the 1980s and 1990s was the result of financial conditionalities imposed through structural adjustment, then the ensuing decade has seen a global policy shift that has profoundly changed the conditions under which academic work is carried out. Particular attention is paid to the manner in which the changing, economically-driven constraints on academic freedom, institutional autonomy and conditions of service in higher educational institutions are mediated by other social conditions such as gender inequalities, the HIV/AIDS crisis, the effects of long- term brain drain and the manner in which local capacity is diverted into survivalism. I argue that higher education reforms threaten to undermine the material base for academic life by emphasising privatisation and cost recovery in contexts where poverty is a major feature of life. Exaggerated concerns with “efficiency” and “ex- cellence” lead to increased regulation and surveillance of scholarly output, render- ing academic freedom vulnerable to formulaic measures of performance that may be insensitive to the work of African academics. The paper concludes by recom- mending a programme of activities designed to re-affirm the public stake in higher education, strengthen and diversify independent scholarly work and encourage Af- rican governments to adopt policies that will strengthen the tertiary sector and en- sure an enabling environment for intellectual development and freedom.